2017
DOI: 10.1016/j.ecl.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Bone–Fat Interaction

Abstract: SYNOPSIS Marrow adipose tissue (MAT) is a recently identified endocrine organ capable of modulating a host of responses. Given its intimate proximity to the bone microenvironment, the impact marrow adipocytes exert on bone has attracted much interest and scientific inquiry. While many questions and controversies still remain relative to marrow adipocytes, multiple conditions/ disease states in which alterations occur in MAT have provided clues about their function. In general, the consensus in the field is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…Over decades of study, accumulating evidence has demonstrated the reciprocality between osteogenesis and adipogenesis, which is well documented in [ 69 , 70 ]. Increased adipogenesis often leads to decreased osteogenesis, vice versa [ 70 ].…”
Section: Differentiation Balance Of Mesenchymal Stem Cells and Hemmentioning
confidence: 99%
“…Over decades of study, accumulating evidence has demonstrated the reciprocality between osteogenesis and adipogenesis, which is well documented in [ 69 , 70 ]. Increased adipogenesis often leads to decreased osteogenesis, vice versa [ 70 ].…”
Section: Differentiation Balance Of Mesenchymal Stem Cells and Hemmentioning
confidence: 99%
“…As we know, bone is a dynamic tissue undergoing continuous resorbing and forming by osteoblasts and osteoclasts. 13 Besides, the relationship between bone and fat formation in the bone marrow is considered inverse. Imbalance between the formation of osteoblasts and adipocytes may cause bone diseases such as osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes are no longer considered an inert type of cell that just stores fat. It is now clear that adipocytes function as endocrine glands that are capable of synthesizing a number of biologically active compounds that regulate metabolic homeostasis and that have wide‐reaching effects on other organs, such as brain and bone (27, 28); therefore, it is of increasing importance to investigate the regulation of adipogenesis to identify key mediators of adipocyte generation.…”
Section: Discussionmentioning
confidence: 99%